2,2 `-[p-Phenylenebis(methylideneazanediyl)]dipyridinium bis(hydrogensulfate) dihydrate - Gao, S.; Qi, Xiao-Juan; Kong, Li-Li; Ng, S.W. (International Union of Crystallography, 2010)
The cation of the title salt, C18H20N42+center dot 2HSO(4)(-)center dot 2H(2)O, lies on a center of inversion with the mid-point directly in the middle of the p-phenylene ring. Within the hydrogensulfate ion, the S-O(H) bond is the longest of the S-O bonds. The dihedral angle between the central and terminal ring of the cation is 78.6 (2)degrees. In the crystal, the cation, anion and water molecule interact by O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds, generating a three-dimensional network.